Involvement of P2Y1, P2Y6, A1 and A2A Receptors in the Purinergic Inhibition of NMDA-Evoked Noradrenaline Release in the Rat Brain Cortex - Clara Quintas; Jorge Gonçalves; Glória Queiroz (Cells, 2023)
In the cerebral cortex, glutamate activates NMDA receptors (NMDARs), localized in noradrenergic neurons, inducing noradrenaline release that may have a permissive effect on glutamatergic transmission, and therefore, on the modulation of long-term plasticity. ATP is co-released with noradrenaline, and with its metabolites (ADP and adenosine) is involved in the purinergic modulation of electrically-evoked noradrenaline release. However, it is not known if noradrenaline release evoked by activation of NMDARs is also under purinergic modulation. The present study aimed to investigate and to characterize the purinergic modulation of noradrenaline release evoked by NMDARs. Stimulation of rat cortical slices with 30 µM NMDA increased noradrenaline release, which was inhibited by ATP upon metabolization into ADP and adenosine and by the selective agonists of A1 and A2A receptors, CPA and CGS2680, respectively. It was also inhibited by UTP and UDP, which are mainly released under pathophysiological situations. Characterization of the effects mediated by these compounds indicated the involvement of P2Y1, P2Y6, A1 and A2A receptors. It is concluded that, in the rat brain cortex, NMDA-evoked noradrenaline release is modulated by several purinergic receptors that may represent a relevant mechanism to regulate the permissive effect of noradrenaline on NMDA-induced neuroplasticity.